Question
upstudy study bank question image url

4. Find the value of \( x \) \( \begin{array}{lll}\text { (a) }\left(\frac{5}{6}\right)^{3} \times\left(\frac{5}{6}\right)^{5}=\left(\frac{5}{6}\right)^{2 x} & \text { (b) }\left(\frac{7}{9}\right)^{-9} \times\left(\frac{7}{9}\right)^{6}=\left(\frac{7}{9}\right)^{2 x-1} & \text { (c) }\left(5^{-x} \times 4^{-x}\right)=20^{-1} \\ \text { (d) } x \times\left(4^{-2}\right)=\frac{1}{4} & \text { (e) } x(-3)^{3} \div x^{2}=-9 & \text { (f) }\left(\frac{1}{3}\right)^{3} \div\left(\frac{2}{3}\right)^{3}=\left(\frac{1}{2}\right)^{x}\end{array} \)

Ask by Norris Frazier. in India
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The values of \( x \) are: - (a) \( x = 4 \) - (b) \( x = -1 \) - (c) \( x = 1 \) - (d) \( x = 4 \) - (e) \( x = 3 \) - (f) \( x = 3 \)

Solution

We will solve each part step‐by‐step. ───────────────────────────── (a) (5/6)³ × (5/6)⁵ = (5/6)^(3+5) = (5/6)⁸   This equals (5/6)^(2x)   Thus equate exponents: 8 = 2x, so x = 4. ───────────────────────────── (b) (7/9)^(–9) × (7/9)⁶ = (7/9)^(–9+6) = (7/9)^(–3)   This equals (7/9)^(2x–1)   Equate exponents: –3 = 2x – 1   Add 1 to both sides: –2 = 2x   So, x = –1. ───────────────────────────── (c) 5^(–x) × 4^(–x) = (5×4)^(–x) = 20^(–x)   This is equal to 20^(–1)   Thus, –x = –1, so x = 1. ───────────────────────────── (d) x × 4^(–2) = x × (1/4²) = x/16   We have: x/16 = 1/4   Multiply both sides by 16: x = 16/4 = 4. ───────────────────────────── (e) x · (–3)³ ÷ x² = x·(–27) ÷ x² = –27/x   Set up the equation: –27/x = –9   Multiply both sides by x: –27 = –9x   Divide by –9: x = 3. ───────────────────────────── (f) (1/3)³ ÷ (2/3)³ = [(1/3)/(2/3)]³ = (1/2)³   This equals (1/2)^(x)   Then equate exponents: 3 = x, so x = 3. ───────────────────────────── Final Answers:  (a) x = 4  (b) x = –1  (c) x = 1  (d) x = 4  (e) x = 3  (f) x = 3

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

First additional information: In solving exponential equations like these, remember to leverage the properties of exponents! For example, when you multiply two expressions with the same base, you can simply add their exponents. This makes finding \(x\) quite straightforward once you set the exponents equal to each other. Second additional information: Common mistakes include forgetting to apply the negative exponent rule or misplacing parentheses. Always double-check your work to avoid these pitfalls, as minor errors can lead to drastically different solutions! When in doubt, rewriting the equation step-by-step can also clarify any confusion and help ensure accuracy.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy